Phytoplasma infection status survey in plum psyllid (Cacopsylla pruni) population - Bodnár, Dominika; Szalai, Brigitta; Tarcali, Gábor; Viczián, Orsolya; Mergenthaler, Emese (Acta Agraria Debreceniensis, 2019)
European Stone Fruit Yellows (ESFY) phytoplasma disease causes an increasing amount of damage. This is especially true to the Gönci growing region. The insect vector of the disease, which has been shown to have a vector role during transmission experiments, is the plum psyllid (Cacopsylla pruni). In 2018, during the swarming period of plum psyllid, in 3 different settlements (Boldogkőváralja, Nagyvárad and Bekecs) 265 psyllidswere collected, from which 165 were plum psyllid. Molecular biology studies showed 106 individuals infected with phytoplasma, of which 20 were males and 86 were females.